10 Pantun Settings: original compositions based on children’s poems from Malaysia. For combinations of soprano solo, alto solo, SATB chorus, violin, piano four-hands, and two pianos - Aziz, Abdul Razak Abdul (The Asian Centre, wholly owned by the Asian Cultural Heritage Centre Bhd., 2013)
Based on poems extracted from Kalong Buku 1 which were edited Za’ba, and published by Dewan Bahasa dan Pustaka (1964). Used with the permission of Dewan Bahasa dan Pustaka.